Análise de confiabilidade aplicada a estruturas com comportamento não linear - Silva, Renan Gomes da (2016)
E ective solutions are sought in a structural design, with low cost and acceptable security for regulatory standards. With advances in building technologies and the use of advanced computational tools, on can get more and more slender structures, where instability is a factor to be considered in structural design. Thus, there is the need for analysis where no physical and geometrical nonlinearities are considered. There is also a need to quantify the structural safety of these systems, which is obtained by Reliability Analysis. In this context, the objective of this work is to apply reliability analysis techniques to structures with nonlinear behavior and evaluate in which types of structures such e ect in uence the probability of failure and reliability index. To do so, computational routines were developed for the Monte Carlo simulation, which were added to the Mastan structural analysis program. This methodology was created so that more robust and e ective reliability analysis were possible and so results were broadly discussed. Through the numerical examples used, it can be said that the implemented routines are e ective and match the results obtained analytically. These results suggest that for certain types of structures, signi cant di erences were observed in the failure probability obtained through the linear and non-linear analysis, while structures where the lateral or global instability are observed, the linear model underestimates the probability of structural failure , which may lead to an incorrect structure design.